Post-Vaccination Serological Evaluation of COVID-19 in the Population of Kenitra, Morocco - Fellaq , Sara El; Dahou, Badreddine; Rkhaila , Amine; Lachguer, Sara Ait; Bouziani , Amina; Chahboune, Mohammed (Bangladesh Journal of Medical Science, 2025)
Background Severe Acute Respiratory Syndrome Coronavirus 2 (SARSCoV- 2) is responsible for Coronavirus Disease 2019 (COVID-19) and is considered one of the most challenging pandemics of the 21st century. This complex situation has brought together scientists and healthcare professionals to develop new vaccines that are both safe and quick to produce. Method The present study aims to evaluate the effects of COVID-19 vaccination on the serology of 701 patients attending healthcare centers in the province of Kenitra (Rabat-Salé- Kenitra region) based on various demographic and clinical parameters. The types of vaccines administered (Sinopharm, AstraZeneca, Johnson & Johnson, Pfizer) and vaccination schedules were examined, highlighting variations in immune responses. Subsequently, logistic regression analysis was used to assess the contributions of variables such as age, gender, comorbidities, types of vaccines administered, and history of COVID-19 infection. Results Data analysis reveals a slight female predominance among participants (55.9%), a diverse age distribution ([55-60], 12.8%), and a significant prevalence of comorbidities, mainly diabetes and hypertension (49.9% with diabetes). The results showed that age and history of COVID-19 infection had a significant influence on serological responses. Conclusion This finding could help practitioners and public health professionals optimize vaccination strategies for future epidemics. Bangladesh Journal of Medical Science Vol. 24 No. 02 April’25 Page : 478-486